Analysis of the Implementation of the Auction Policy for the Execution of Tax Confiscated Goods at the Bekasi City State Property and Auction Services Office - Alamsyah, Sultan Zainurrofiq (Indonesian Scientific Publication, 2023)
The Tax Execution Auction is an auction conducted by the DGT to carry out the execution of confiscated property of a Taxpayer, the property auctioned and the proceeds become a supporting sector for state financial revenues. This study aimed to identify and analyze the implementation of the Tax Execution Auction policy. This study used the Van Meter and Van Horn theory to explore the results of the study. This study applied a descriptive qualitative method, where researchers collect data through interviews, documentation, and observation. The research location was at the service office of state property and auction Bekasi. The results of this research stated that the implementation of the Tax Execution Auction policy can be said to have not been carried out properly because there are still many obstacles. The obstacles that hinder the implementation of the policy, i.e., the absence of documents or incomplete documents from confiscated auction items and resistance from asset owners and lack of information for the public.